Intravesical explosion during endoscopic transurethral resection of a bladder tumor - Sallami, Sataa; Rhouma, Sami; Dahmani, Adel; Cherif, Karim; Horchani, Ali; Nouira, Yassine (Ibnosina Journal of Medicine and Biomedical Sciences, 2011)
Explosion inside the bladder occurring during transurethral resection is rarely recognized as a complication of endoscopic resection of bladder tumors. We report a case of intravesical explosion during an endoscopic resection of a bladder tumor. Damages to the bladder were minor. We discuss the possible causes of this complication as well as the different preventive measures. A focused review of the English literature is given.
Keywords: bladder neoplasms; transurethral resection; bladder injuries; intraoperative complications - incident – accident